Evaluation of in vitro wound healing efficacy of breadfruit derived starch hydrolysate - Mohamed Amin, Zahiah; Koh, Soo Peng; Tan, Chin Ping; Yeap, Swee Keong; Abdul Hamid, Nur Syazwani; Long, Kamariah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
To study the wound healing efficacy of breadfruit starch hydrolysate, an in vitro wound scratch assay was conducted, in which the migration rate of wounded NIH 3T3 fibroblasts was determined. Wounds treated with lower dextrose equivalent (DE), (DE 10-14) starch hydrolysate were found capable to improve the wound healing of NIH 3T3 fibroblast cell with the percentage of wound closure improvement of 77%, respectively when compared with higher DE range (DE 15-19 and DE 20-24). The findings obtained in the BrdU uptake and MTT viability assays confirmed the wound healing properties of breadfruit starch hydrolysate as the starch hydrolysate-treated wounded NIH 3T3 fibroblasts were able to proliferate well and no cytotoxicity was observed. Together, these findings indicated that the newly developed breadfruit starch hydrolysate performed better than commercial (COM) starch hydrolysate of the same DE ranges. In conclusion, breadfruit starch hydrolysate had better functional properties than did starch hydrolysates derived from other sources and that they could play a beneficial role in wound healing applications.